Review of impression creep test: a small-scale testing method for evaluation of creep properties of materials - Naveena,; Mathew, M. D.; Komazaki, Shin-Ichi (Frontiers in Materials, 2025)
Creep is a critical mechanical property essential for materials intended for components and structures that operate under sustained loads at elevated temperatures over extended periods. Traditionally, the creep behavior of materials is evaluated through uniaxial creep tests performed on standardized specimens following internationally recognized testing procedures. However, these conventional tests require a substantial amount of material to generate comprehensive data for understanding creep behavior and for developing design databases. The Impression Creep (IC) test presents an alternative, minimally invasive approach for characterizing the creep properties of metallic materials. In this method, a constant compressive load is applied to a flat specimen using a flat-ended cylindrical or rectangular punch, and the penetration depth over time is recorded to assess the material’s creep deformation response. The IC method offers several advantages over standard techniques, including the ability to extract a large volume of data from a single specimen, thereby minimizing specimen preparation efforts and sample-to-sample variability. Moreover, as the test induces only a localized indentation without fracturing the specimen, it is considered nearly non-destructive. Significant research efforts are ongoing to optimize aspects such as specimen and machine design, testing protocols, data interpretation methods, and constitutive modeling, while also striving to establish correlations between IC-derived parameters and those obtained from conventional creep tests. This paper presents a comprehensive review of past research on IC testing, identifies existing knowledge gaps, and highlights key challenges based on the authors’ extensive experimental and modeling investigations alongside a critical analysis of the broader literature.